Pre-frailty, frailty and associated factors in older caregivers of older adults - Máximo,Roberta de Oliveira (2020)
ABSTRACT INTRODUCTION Providing care to an older adult is an activity that requires considerable physical effort and can cause stress and psychological strain, which accentuate factors that trigger the cycle of frailty, especially when the caregiver is also an older adult. However, few studies have analyzed the frailty process in older caregivers. OBJECTIVES To investigate the prevalence of pre-frailty, frailty and associated factors in older caregivers of older adults. METHODS A cross-sectional study was conducted including 328 community-dwelling older caregivers. Frailty was identified using frailty phenotype. Socio-demographic, behavioral and clinical aspects, characteristics related to care and functioning were covariables in the multinomial logistic regression. RESULTS The prevalence of pre-frailty and frailty were 58.8% and 21.1%, respectively. An increased age, female sex, not having a conjugal life, depressive symptoms and pain were commonly associated with pre-frailty and frailty. Sedentary lifestyle was exclusively associated with pre-frailty, whereas living in an urban area, low income and the cognitive decline were associated with frailty. A better performance on instrumental activities of daily living reduced the chance of frailty. CONCLUSION Many factors associated with the frailty syndrome may be related to the act of providing care, which emphasizes the importance of the development of coping strategies for this population.